The structure of application«SMART NEWS» and usage as information resource (Herald of Journalism, 2018)
In the article we give information about new mobile application, which made by Kazakh developers named “Smart News”. You can find large information about steps in developing process, also about ways of usage the application. Main advantage of the mobile application is that, we collect in one touch all kind of new media. On the other hand, the application gives new motivation to traditional media in progress with the time and technology to be closer to auditory.120 Хабаршы. Журналистика сериясы. №2 (48). 2018“SMART NEWS” бaғдaрлaмaсыныңқұрылымымен aқпaрaт тaрaтудaғы қолдaнысыXXI century is the era of information and high technologies. Therefore, in order not to miss the newsflow, we should go in step with time. Creating cultural and economic ties with important informationon the Internet, it is currently distributed hourly basis. Unfortunately, not every citizen of our countrycan access it immediately. To do this, there are lots of reasons. One of these reasons is the restrictionof the right opportunities. The second reason is that the flow of information is often printed in English.Translation from English into Russian, from Russian into Kazakh language performed for a long time, thusaccess to the flow of information comes later. Unfortunately, our people now spend a lot of time onsocial networks.According to statistical data of foreign citizens of Europe, read the newspaper in the subway hasbecome a habit. The main goal is to increase interest in reading, learning and getting information to thepeople. Essence of my program is due to advanced technology and smart phones to increase people’sinterest in reading. The main purpose of the special team set up to receive and translate foreign publicationswithin the last posts of social needs, distributed among readers. Of course, there are many programsthat are broadcast today; to differ, and not only have their own signature to awaken interest willalso be visual design features.Key words: media, technology, development, information, auditory, news, mobile application.